Determinant factors for giving the diphtheria, pertussis, and tetanus immunization in West Java Province 2017 - Nur Hairunnisa; Besral Besral (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: DPT-HB immunization is one of the mandatory basic immunizations given to children to prevent diphtheria, pertussis (whooping cough) and tetanus. In 2017, West Java was one of the provinces that reported Diphtheria Outbreaks with 14 deaths from 153 cases. This study aims to determine the relationship of parental education, area of residence, visits to health care facilities and insurance ownership of the provision of DPT-HB Immunization in children in West Java Province.Method: The study design was cross sectional. The sample in this study was based on secondary children record data of the 2018 IDHS consisting of DPT-HB/Pentavalent immunization; parental education; residential area; visits to health care facilities and ownership of health insurance.Results: The results of this study were obtained between parental education (p value: 0,0001, OR: 2,084) and the area of residence (p value: 0,028, OR: 0,637) having a relationship with DPT-HB / Pentavalent immunization.Conclusion: Parental education has the strongest relationship with the provision of DPT-HB / Pentavalent immunization in children. Better education will have a positive effect on increasing knowledge and changing behavior in preventing infectious diseases such as by providing complete immunization to children.